PENGGUNAAN METODE ROLE PLAYING TERHADAP MINAT DAN HASIL BELAJAR BIOLOGI SISWA KELAS X MA ADDINUL QAYYIM KAPEK GUNUNGSARI TAHUN PELAJARAN 2010/2011 - Safnowandi Safnowandi (Jurnal Ilmiah Mandala Education (JIME), 2016)
Its low achievement learn the Biology is cause of less compatible strategy learn used in each discussion fundamental. Therefore, teachers require to creating the better study that is Role Playing. This research target is to know the use of Role Playing method can improve the enthusiasm and result of learning student of class X at Biology lesson in MA Addinul Qayyim Kapek Gunungsari at School Year 2010/2011. This subject research is class Xd. Research type which is used was Research of Class Action (PTK) which is executed in 2 cycles and for each cycle consisted of the planning, action execution, observation and reflection. Techniques of data collected by enquette and test. Research instrument used by enquette to know the enthusiasm of students learn by using Role Playing method. And test to see the result of students learn. Result of this research indicate that at the first cycle, show the complete percentage of classical equal to 51,85%, and enthusiasm learn of the students equal to 30,14. At the second cycle, complete percentage of classical equal to 85,18%, and enthusiasm learn the students equal to 32,77 with the high category. So we can concluded that, use of Role Playing method can improve the enthusiasm and result of student learn class X at Biological subject in MA Addinul Qayyim Kapek Gunungsari in the School Year 2010 / 2011